Thyroid hormonal disturbances related to treatment of hepatitis C with interferon-alpha and ribavirin - Danilovic, Debora Lucia Seguro; Mendes-Correa, Maria Cassia; Chammas, Maria Cristina; Zambrini, Heverton; Marui, Suemi (Clinics (São Paulo, Brazil), 2011)
To characterize thyroid disturbances induced by interferon-alpha and ribavirin therapy in patients with chronic hepatitis C. Interferon-alpha is used to treat chronic hepatitis C infections. This compound commonly induces both autoimmune and non-autoimmune thyroiditis. We prospectively selected 26 patients with chronic hepatitis C infections. Clinical examinations, hormonal evaluations, and color-flow Doppler ultrasonography of the thyroid were performed before and during antiviral therapy. Of the patients in our study, 54% had no thyroid disorders associated with the interferon-alpha therapy but showed reduced levels of total T3 along with a decrease in serum alanine aminotransferase. Total T4 levels were also reduced at 3 and 12 months, but free T4 and thyroid stimulating hormone (TSH) levels remained stable. A total of 19% of the subjects had autoimmune interferon-induced thyroiditis, which is characterized by an emerge of antithyroid antibodies or overt hypothyroidism. Additionally, 16% had non-autoimmune thyroiditis, which presents as destructive thyroiditis or subclinical hypothyroidism, and 11% remained in a state of euthyroidism despite the prior existence of antithyroidal antibodies. Thyrotoxicosis with destructive thyroiditis was diagnosed within three months of therapy, and ultrasonography of these patients revealed thyroid shrinkage and discordant change in the vascular patterns. Decreases in the total T3 and total T4 levels may be related to improvements in the hepatocellular lesions or inflammatory changes similar to those associated with nonthyroidal illnesses. The immune mechanisms and direct effects of interferon-alpha can be associated with thyroiditis. Interferon-alpha and ribavirin induce autoimmune and non-autoimmune thyroiditis and hormonal changes (such as decreased total T3 and total T4 levels), which occur despite stable free T4 and TSH levels. A thyroid hormonal evaluation, including the analysis of the free T4, TSH, and antithyroid antibody levels, should be mandatory before therapy, and an early re-evaluation within three months of treatment is necessary as an appropriate follow-up.